DRB1 locus alleles of HLA class II are associated with modulation of the immune response in different serological profiles of HIV-1/Epstein-Barr virus coinfection in the Brazilian Amazon region - Pereira, Leonn Mendes Soares; dos Santos França, Eliane; Costa, Iran Barros; Lima, Igor Tenório; Jorge, Erika Vanessa Oliveira; de Souza Mendonça Mattos, Patrícia Jeanne; Freire, Amaury Bentes Cunha; de Paula Ramos, Francisco Lúzio; Monteiro, Talita Antonia Furtado; Macedo, Olinda; Sousa, Rita Catarina Medeiros; Freitas, Felipe Bonfim; et al. (Frontiers in Medicine, 2024)
Background Epstein–Barr virus (EBV) infection involves distinct clinical and serological profiles. We evaluated the frequency of alleles of locus DRB1 of HLA class II in different serological profiles of EBV infection among HIV-1 infected patients. Methods We recruited 19 patients with primary infection, 90 with serological transition and 467 with past infection by EBV, HIV-1 co-infection was 100% in primary infection and approximately 70% in other serological profiles. EBV viral load was quantified by real-time PCR, T lymphocyte quantification and cytokine level analysis were performed by flow cytometry, and HLA locus genotyping was performed by PCR-SSO. Results The DRB1*09 allele was associated with primary infection (p: 0.0477), and carriers of the allele showed changes in EBV viral load (p: 0.0485), CD8(+) T lymphocyte counts (p: 0.0206), double-positive T lymphocyte counts (p: 0.0093), IL-4 levels (p: 0.0464) and TNF levels (p: 0.0161). This allele was also frequent in HIV-coinfected individuals (p: 0.0023) and was related to the log10 HIV viral load (p: 0.0176) and CD8(+) T lymphocyte count (p: 0.0285). In primary infection, the log10 HIV viral load was high (p: 0.0060) and directly proportional to the EBV viral load (p: 0.0412). The DRB1*03 allele correlated with serological transition (p: 0.0477), EBV viral load (p: 0.0015), CD4(+) T lymphocyte count (p: 0.0112), CD8(+) T lymphocyte count (p: 0.0260), double-negative T lymphocyte count (p: 0.0540), IL-4 levels (p: 0.0478) and IL-6 levels (p: 0.0175). In the serological transition group, the log10 HIV viral load was high (p: 0.0060), but it was not associated with the EBV viral load (p: 0.1214). Past infection was related to the DRB1*16 allele (p: 0.0477), with carriers displaying IgG levels (p: 0.0020), CD4(+) T lymphocyte counts (p: 0.0116) and suggestive CD8(+) T count alterations (p: 0.0602). The DRB01*16 allele was also common in HIV-1 patients with past EBV infection (p: 0.0192); however, the allele was not associated with clinical markers of HIV-1 infection. Conclusion Our results suggest that HLA class II alleles may be associated with the modulation of the serological profiles of the immune response to Epstein-Barr virus infection in patients coinfected with HIV-1.